Towards highly stable lithium sulfur batteries: Surface functionalization of carbon nanotube scaffolds. (May 2018) - Kim, Patrick Joo Hyun; Kim, Kyungho; Pol, Vilas G.
Abstract: In order to alleviate the systemic challenges underlying in Lithium sulfur (Li-S) batteries, the surface of non-polar carbon materials have been widely modified with functional polymeric materials and metal-oxide compounds to chemically interact with polysulfides and thus improve the cycle performance of sulfur cathodes. However, the inherent low conductivity and long-term instability of functional polymers and ceramic materials impede the efficient electrochemical reactions and, in the end, deteriorate the electrochemical performances of Li-S batteries. In this study, we demonstrated a facile and effective approach to customize the surface characteristics of carbon nanotubes (CNTs) via thermal treatments under different atmospheres (oxygen and hydrogen) and exploit these properties for sulfur reservoirs and interlayer barrier in order to enhance the electrochemical performances of Li-S batteries. With the aid of different characteristics of modified CNTs, electrochemical performances of sulfur cathodes were effectively optimized in terms of specific capacity and cycling performance. In addition, when interlayers were coupled with general sulfur cathodes with high sulfur loading mass (2.5 mg cm −1 ), it also showed analogous trends in improving the specific capacity and cycle performance (250 cycles). Graphical abstract: Image 1